AN ANALYSIS OF CODE-SWITCHING IN THE MOVIE “ENCANTO" - Aliyah Nadhifa Lawani; Nurul Fadhillah; Muhammad Ilham (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Code-switching is a common event of switching from one language to another. This research is conducted with the purpose of studying code-switching sequences in the movie ‘Encanto’. The methods of research that are used in this study are data collecting and descriptive analysis. The result reveals that the movie consists of many code-switching between the language English and Spanish. There are three types of code-switching that appeared in the movie; tag-switching, intersentential switching, and intrasentential switching. The most frequently used type is intrasentential switching which is 84,61% compared to tag and intersentential switching which only have 9,25% and 6,25% respectively